2005
DOI: 10.1007/s11936-005-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Rate versus rhythm control strategies for AF

Abstract: The safest long-term management strategy for elderly patients with persistent or recurrent episodes of atrial fibrillation (AF) is careful rate control with medications in conjunction with appropriate oral warfarin anticoagulation. Atrioventricular junctional ablation, with pacemaker implantation, may be necessary in patients who cannot have their rate controlled adequately, or have marked fluctuations in rate with standard medical therapies. Maintenance of sinus rhythm with repeat cardioversions, antiarrhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Left atrial enlargement has been shown to be associated with an inversed rate of AF recurrence after chemical or electrical cardioversion [4] . Previous studies have shown that an increase in the LA diameter is associated with higher AF prevalence; moreover LA diameter is an independent risk factor in the development of AF, and in determining the long-term outcomes of ablation [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Left atrial enlargement has been shown to be associated with an inversed rate of AF recurrence after chemical or electrical cardioversion [4] . Previous studies have shown that an increase in the LA diameter is associated with higher AF prevalence; moreover LA diameter is an independent risk factor in the development of AF, and in determining the long-term outcomes of ablation [5] .…”
Section: Introductionmentioning
confidence: 99%